The Neurosciences of Health Communication: An fNIRS Analysis of Prefrontal Cortex and Porn Consumption in Young Women for the Development of Prevention Health Programs - Cuesta, Ubaldo; Niño, Jose Ignacio; Martinez, Luz; Paredes, Borja (Frontiers in Psychology, 2020)
This work explores using the fNIRS neuroimaging technique using young university women with different levels of consumption of pornography, the activation of the prefrontal cortex (cue reactivity) when viewing a pornographic clip (cue exposure) versus a control clip. The results indicate that the viewing of the pornographic clip (vs. control clip) causes an activation of Broadmann's area 45 of the right hemisphere (BA 45, pars triangularis) (p <.01). An effect also appears between the level of self-reported consumption and the activation of right BA 45: the higher the level of self-reported consumption, the greater the activation (p <.01). On the other hand, those subjects who have never consumed pornographic material do not show activity of the right BA 45 compared to the control clip (p <.01) indicating a qualitative difference between non-consumers and consumers. These results are consistent with other research made in the field of addictions. It is hypothesized that the mirror neuron system may be involved, through the mechanism of empathy, which could provoke vicarious eroticism. Finally, we suggest the applications that these results may have for primary and secondary prevention programs in the field of problematic consumption of pornography.